Impact of Time to Treatment Initiation in Patients with Human Papillomavirus-positive and -negative Oropharyngeal Squamous Cell Carcinoma. Issue 6 (June 2018) - Grønhøj, C.; Jensen, D.; Dehlendorff, C.; Nørregaard, C.; Andersen, E.; Specht, L.; Charabi, B.; von Buchwald, C.
Abstract: Aims: The distinct difference in disease phenotype of human papillomavirus-positive (HPV+) and -negative (HPV–) oropharyngeal squamous cell cancer (OPSCC) patients might also be apparent when assessing the effect of time to treatment initiation (TTI). We assessed the overall survival and progression-free survival (PFS) effect from increasing TTI for HPV+ and HPV– OPSCC patients. Materials and methods: We examined patients who received curative-intended therapy for OPSCC in eastern Denmark between 2000 and 2014. TTI was the number of days from diagnosis to the initiation of curative treatment. Overall survival and PFS were measured from the start of treatment and estimated with the Kaplan–Meier estimator. Hazard ratios and 95% confidence intervals were estimated with Cox proportional hazard regression. Results: At a median follow-up of 3.6 years (interquartile range 1.86–6.07 years), 1177 patients were included (59% HPV+). In the adjusted analysis for the HPV+ and HPV– patient population, TTI influenced overall survival and PFS, most evident in the HPV– group, where TTI >60 days statistically significantly influenced overall survival but not PFS (overall survival: hazard ratio 1.60; 95% confidence interval 1.04–2.45; PFS: hazard ratio 1.46; 95% confidence interval 0.96–2.22). For patients with a TTI >60 days in the HPV+ group, TTI affected overall survival and PFS similarly, with slightly lower hazard ratio estimates of 1.44 (95% confidence interval 0.83–2.51) and 1.15 (95% confidence interval 0.70–1.88), respectively. Conclusion: For patients treated for a HPV+ or HPV– OPSCC, TTI affects outcome, with the strongest effect for overall survival among HPV– patients. Reducing TTI is an important tool to improve the prognosis. Highlights: TTI affects outcome for both HPV+ and HPV– oropharyngeal cancer patients. TTI has the strongest impact for OS among HPV– patients waiting > 60 days. Reducing the diagnostic or treatment initiation delay is an essential tool to improve the prognosis for oropharyngeal cancer patients.